2012
DOI: 10.31018/jans.v4i1.234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of geospatial variability of fluoride contamination in ground water of Mathura District, Uttar Pradesh, India

Abstract: Abstract:Groundwater is one of the major sources of water in arid and semi-arid regions. Groundwater quality data and its spatial distribution are important for the purpose of planning and management. Geo-statistical methods are one of the most advanced techniques for interpolation of groundwater quality. In this study, kriging methods were used for predicting the spatial distribution of fluoride content in groundwater. Data were collected from 13 wells in Mathura district (Uttar Pradesh, India). After normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…It is controlled by carbon-dioxide, carbonate and bicarbonate equilibrium. The combination of CO 2 with water form carbonic acid affects the pH of the water (Rawat et al 2012(Rawat et al , 2013. If the pH is not within the prescribed limits, it damages mucous membrane present in eyes, nose, mouth, abdomen, anus, etc.…”
Section: Results From Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It is controlled by carbon-dioxide, carbonate and bicarbonate equilibrium. The combination of CO 2 with water form carbonic acid affects the pH of the water (Rawat et al 2012(Rawat et al , 2013. If the pH is not within the prescribed limits, it damages mucous membrane present in eyes, nose, mouth, abdomen, anus, etc.…”
Section: Results From Statistical Analysismentioning
confidence: 99%
“…EC in water is due to ionization of dissolved inorganic solids. EC is a measure of water capacity to convey electric current (Rawat et al 2012(Rawat et al , 2013. It is used to estimate the amount of dissolved solids.…”
Section: Results From Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both parameters followed a log-normal distribution and demonstrated a moderate spatial dependence according to the nugget ratio. Other similar studies have shown that geostatistical approach is a suitable method for estimation of aquifer hydraulic properties (Doctor and Nelson, 1981;Sophocleous et al, 1982;Nunes et al, 2004a;Arslan, 2012Arslan, , 2013Rawat et al, 2012;Varouchakis et al, 2012;Delbari, 2013). Thus, to achieve the purpose of this study, the core objectives consists of variographic analysis of the spatial variability of groundwater parameters H and WTD, the generation of maps of kriged estimates of logH and log(WTD), and back transforms of logH and log(WTD) to H and WTD to assess the H and WTD fields.…”
Section: Introductionmentioning
confidence: 99%
“…It is the best linear unbiased estimator spatial distribution analysis; it is also recommended by environmental protection agency that kriging would be more accurate option for water quality studies (Gundogdu et al, 2007, Uyan et al, 2010. Kriging is an advance method of geospatial procedure for interpolation which generates an estimated surface from the distance and direction between sample points which reflects spatial correlation (Rawat et al, 2012). This method becomes appropriate where there is know there is a spatially correlated distance or directional prejudice in the data like with down flowing of the river makes it dirtier.…”
Section: Gis Integrationmentioning
confidence: 99%